Level of Compliance and Fishermen's Perceptions on Sustainable Fishery at UPT Fish Port, Dumai City, Riau Province - Cundaningrum, Laksita; Rengi, Pareng; Zain, Jonny (Journal of Coastal and Ocean Sciences, 2022)
Research has been carried out at the Fishery Port UPT Dumai City, Riau Province which aims to describe the socio-economic characteristics of fishermen, determine the level of compliance of fishermen, fishermen's perceptions of the criteria for environmentally friendly fishing gear, fishermen's perceptions of the existence of fish resources and see a comparison of compliance and perceptions of fishermen in UPT Fishery Port Dumai City, Riau Province. This type of research is descriptive research with a survey method. The sample used is 33 respondents with sampling technique. Data collection techniques were carried out by means of observation and interviews using questionnaires to respondents. The analysis used is descriptive, comparative analysis using the Kruskal-Wallis test and the Mann-Whitney test, and correlation analysis using the Spearman rank correlation. The results of this study indicate that the socio-economic characteristics of fishermen in the Fisheries Port UPT, Riau Province, are the majority of fishermen aged 36-45 with low education, namely basic education. Experience as a fisherman for more than 15 years. Then for the characteristics of fishermen in the income section, the dominant fishermen earn above the UMP as many as 20 people. Finally, for fishermen, the most dependents are 3-4 dependents as many as 15 people with a percentage of 45.46%. Gill net fishermen have the highest compliance compared to splints and sondong while the lowest compliance is sondong fisherman. There is no significant difference in fishermen's perceptions of environmentally friendly fishing gear and fishermen's perceptions of the existence of fish resources